THE EFFECT OF SMARTPHONE USE ON STUDENT LEARNING INTEREST AND STUDENT PROCRASTINATION BEHAVIOR AT SMK X TANGERANG CITY - marsepa, Eva; Kusumastuti, Nurry Ayuningtyas; Mufrokah, Oka Solehatul (Jurnal Ilmiah Global Education, 2023)
This research was conducted by researchers because it was motivated by several phenomena that occurred at SMK X Kota Tangerang, namely the use of smartphones which resulted in less interest in learning and increased student procrastination behavior. as a result of using a smartphone so that the test or test scores drop, submitting assignments not on time or not submitting assignments at all, looking for answers to exams or tests using a smartphone, when in the online learning process there are often students who disappear from online learning because they are preoccupied with activities on smartphones either whether playing games or other social media, when offline learning takes place there are students who are engrossed in playing smartphones so they don't listen to the teacher's explanation. The formulation of the problem in this study is how much is the use of smartphones for students at SMK X Tangerang City, how much is the interest in learning students at SMK X Tangerang City, how much is the procrastination behavior of students at SMK X Tangerang City, is there any effect of using smartphones on students' learning interest in SMK X Kota Tangerang, is there any effect of smartphone use on students' procrastination behavior at SMK X Kota Tangerang. The results of the research conducted are the use of smartphones by 81% of respondents including the medium category, student learning interest of 66% of respondents in the medium category, student procrastination behavior of 49% of respondents in the low category, there is a significant influence between the use of smartphones on student interest in learning and a significant value of 0.040 <0.050 and tcount of 2.088 is greater than ttable (1.99), there is a significant effect between smartphone use on students' procrastination behavior at SMK X Kota Tangerang with a significant value of 0.000 <0.05 and tcount of 3.776 bigger than ttable (1.99).